Project brief for IIUM Hospital (Phase 1), International Islamic University Malaysia (Medical Campus)Kuantan, Pahang Darul Makmur - Mohd Nawawi, Norwina; Sapian, Abdul Razak; Abdul Rani, Mohammed Fauzi (Unit Kerjasama Awam Swasta, 2009)

(untitled)
A project brief on medical requirements for the planning and design of IIUM teaching hospital in IIUM Kuantan Campus. There are two versions of the brief, i.e. the 2009 version and the 2010 version. The march 2010 version was revised after the site visit was made to Kuantan by the bidders and as an outcome of the dialogue.